Coping with sexual orientation microaggressions: Implications for psychological distress and alcohol use. Issue 3 (3rd July 2018) - Scharer, Jacob L.; Taylor, Matthew J.
ABSTRACT: This study examined the impact of sexual orientation microaggressions on psychological distress and alcohol use. Five different coping styles were assessed as mediators of the relationship between exposure to microaggressions and psychological distress, and between microaggressions and alcohol-related problems. Participants were 229 gay, lesbian, and bisexual individuals who completed an online questionnaire. Experiencing microaggressions was significantly associated with more psychological distress and alcohol problems. Internalization and detachment coping styles mediated the relationship between microaggressions and psychological distress. However, none of the coping styles examined in this study mediated the relationship between microaggressions and alcohol problems. Implications for clinical practice and research are addressed.